Syntheses of Specifically 15N‐Labeled Adenosine and Guanosine. Issue 12 (19th December 2022) - Jones, Roger A.; Gaffney, Barbara L.
Abstract: This article describes the specific incorporation of 15 N into the N7 and amino positions of adenosine (Basic Protocol 1), and conversion of the adenosine to guanosine labeled at the N1, N7, and amino positions (Basic Protocol 2). Two variations of the procedures are also presented that include either 12 C or 13 C at the C8 position of adenosine, and 13 C at either the C8 or C2 position of guanosine. These 13 C tags permit the incorporation of two 15 N‐labeled nucleosides into an RNA strand while ensuring that their nuclear magnetic resonance (NMR) signals can be distinguished from each other by the presence or absence of C‐N coupling. While the major application of these specifically 15 N‐labeled nucleosides is NMR, the additional mass makes them useful in mass spectrometry (MS) as well. The procedures can also be adapted to synthesize the labeled deoxynucleosides. The Support Protocol describes the synthesis of 7‐methylguanosine. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Syntheses of [7, NH2 ‐ 15 N2 ]‐ and [8‐ 13 C‐7, NH2 ‐ 15 N2 ]adenosine Support Protocol : Synthesis of 7‐methylguanosine Basic Protocol 2 : Synthesis of [2‐ 13 C‐1, 7, NH2 ‐ 15 N3 ]‐ and [8‐ 13 C‐1, 7, NH2 ‐ 15 N3 ]guanosine